Large-area transparent Sb-based and perovskite-doped scintillator material and preparation method and application thereof
By introducing large sterically hindered organic cations into the Sb-based perovskite scintillator material, the glass-based transparent perovskite scintillator problem is solved, and high-resolution radiation imaging is achieved.
Patent Information
- Application Number
- CN202311365233.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-20
AI Technical Summary
The existing Sb-based perovskite scintillation screens have the problem of strong light scattering, which limits its application in X-ray imaging.
By introducing organic cation R-C18H15P+ with large steric hindrance into the Sb-based and its doped perovskite structure, a glass-state transparent perovskite scintillator material is formed, reducing light scattering and improving spatial resolution.
It achieves high transparency and low light scattering, improves the resolution of ray imaging, and can reach 25lp/mm, and is suitable for large-area ray detection and other fields.
Smart Images

Figure CN119859159A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite scintillator materials, and more specifically, to a large-area transparent Sb-based and doped perovskite scintillator material, and a preparation method and application thereof. Background Art
[0002] Common rays include α, β, γ rays, x-rays and neutron rays. Rays not only have application prospects in scientific research, but also have great application potential in daily fields such as security inspection, medical imaging and industrial flaw detection. The emergence of ray detectors is the premise and basic guarantee for the application of rays in the detection field. Ray detectors are generally divided into direct detectors and indirect detectors. Compared with direct detectors, the advantages of indirect detectors are low price and fast response speed, which can be used for dynamic imaging. Scintillator is the key component of indirect detectors. Currently, the commonly used ray scintillators are mainly inorganic scintillators such as Gd2O2S:Tb, AgZnS, CsI:Tl and LYSO:Ce. However, most inorganic scintillators are bulk crystals, with harsh preparation conditions and high prices, and extremely high requirements for equipment. Another disadvantage is that the luminescence center of most inorganic scintillators is a dopant, whose transition energy is fixed, and cannot produce tunable scintillation, and cannot perform color ray imaging. In addition, the crystals produced under high temperature conditions are fragile and the preparation process of large-area thin-film scintillators is complicated, which seriously limits their application in large-area X-ray imaging and flexible X-ray detection.
[0003] In recent years, researchers have found that perovskite materials have advantages such as adjustable band gap and high quantum yield, and have outstanding advantages in the field of indirect detection. For example, the disclosed all-inorganic perovskite nanocrystal scintillator containing Cs and Pb has realized the color luminescence display of X-rays for the first time, indicating that the perovskite scintillator has the advantage of tunable luminescence wavelength. Existing reports also include: two-dimensional perovskite scintillators that can be used for β-ray monitoring, and by combining lanthanide-doped perovskite scintillators with flexible substrates, transparent flexible films that can be used for 3D imaging have been prepared, breaking the inherent limitations of traditional X-ray flat-panel detectors. In addition, the hydrogen-rich 2D perovskite Mn-(C 18 H 37 The radiation performance of (NH3)2PbBr4 under fast neutrons has a resolution of 0.5lp / mm. The (ETP)2MnBr4 transparent medium and (HTPP)2MnBr4 transparent medium prepared by melting method have high transmittance in the luminescence band, and the X-ray resolution is greater than 10lp / mm.
[0004] Sb-based perovskites have the advantages of high quantum yield and large X-ray absorption coefficient, and are considered to be potential excellent scintillators. The reported X-ray light yield of (PPN)2SbCl5 single crystal is close to that of commercial scintillator CsI:Tl, which is about 49000ph MeV. -1 The reported C 50 H 44 P2SbCl5 crystals were blended with PMMA to prepare a scintillator screen with a spatial resolution of 8.2lp / mm. Currently reported Sb-based perovskite scintillators are all blended with binders to form films for radiographic imaging. This type of imaging screen has a low transmittance and strong light scattering, which is not conducive to clear imaging in X-ray imaging. Summary of the invention
[0005] In view of the problem of strong light scattering of the existing Sb-based perovskite scintillator screen, the purpose of the present invention is to provide a large-area transparent Sb-based and doped perovskite scintillator material and its preparation method and application. The perovskite scintillator material not only has the advantages of high quantum yield and large X-ray absorption coefficient, but also introduces organic cations with large steric hindrance into the Sb-based and doped perovskite structure in its structure, and obtains a large-area transparent Sb-based perovskite with controllable shape for the first time, which can be used in the fields of ray detection, etc., to obtain highly clear ray imaging with a resolution of up to 25lp / mm.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A large-area transparent Sb-based and doped perovskite scintillator material, wherein the perovskite scintillator has a general formula of: (RC 18 H 15 P)2Sb y M 1-y X5;
[0008] Wherein, R is selected from one or more of -CH3, -CH2Cl, -CH2CH3, -CH2OCH3, -(CH2)3CH3, -CH2C6H4CH3 and -C6H5;
[0009] The M is a metal ion selected from the B-site doping ions;
[0010] The X is selected from Cl - Br - and I - One or more of the following;
[0011] The y is selected from 0-1, and is not 0.
[0012] In the structure of the large-area transparent Sb-based and doped perovskite scintillator materials, RC 18 H15 P + The large steric hindrance is conducive to the formation of glassy transparent perovskite, whose transparency is as high as 85% in the luminescent band, which can effectively reduce light scattering and improve spatial resolution; the metal ion Sb at the B position 3+ and M 3+ As the luminescence center, it avoids self-absorption and improves the optical performance; the main metal ion at the B position is Sb 3+ , M metal ions are doped ions at the B site. This setting can avoid self-absorption and improve optical properties.
[0013] The large-area transparent Sb-based and its doped perovskite scintillator material can absorb rays and then convert X-ray photons into visible light. Some neutron scintillators need to be combined with neutron absorbers (such as polymer PS, etc.), which absorb neutrons through neutron absorbers, and then transfer the converted neutron energy to the luminescent body to emit light, which is an energy transfer process.
[0014] Furthermore, the thickness of the perovskite scintillator material is 0.05-1.0 cm.
[0015] Further, the M is selected from Bi 3+ 、In 3+ and Eu 3+ One or more of the .
[0016] In another aspect, the present invention provides a method for preparing the perovskite scintillator material as described above, wherein the perovskite scintillator material is prepared by a melting method.
[0017] Furthermore, the preparation method comprises the following steps:
[0018] The RC with a molar ratio of 2:y:1-y 18 H 15 Solid raw materials of PX, SbX3 and MX3 are ground into powder and mixed to obtain a mixture;
[0019] The mixture is heated until all the solid powder is converted into a molten mixture;
[0020] Cooling the molten mixture in a mold to obtain the perovskite scintillator material;
[0021] Wherein, the definitions of y, R, X, and M are as described above.
[0022] Furthermore, the mixture is placed in a high temperature resistant container and then heated. The high temperature resistant container includes but is not limited to one or more selected from a crucible, a glass container, and an iron pot.
[0023] Furthermore, the heating temperature ranges from 100 to 350°C.
[0024] Furthermore, the heating time is 1-4h.
[0025] Furthermore, the cooling method includes but is not limited to natural cooling, air cooling or liquid cooling, and the cooling time is 5-15 minutes.
[0026] Furthermore, the mold is selected from one or more of a graphite mold, a silicone mold, a silicon sheet, an aluminum sheet and ceramics.
[0027] The perovskite scintillator material obtained in the above preparation method not only has good self-support, but also the shape and thickness of the final product can be controlled by controlling the shape of the mold and the volume of the melt poured in. The controllability of the product shape and thickness shows great potential in practical applications.
[0028] In yet another aspect, the present invention provides application of the perovskite scintillator material as described above in the field of radiation detection imaging.
[0029] Furthermore, the rays are selected from one or more of soft X-rays, hard X-rays and neutrons.
[0030] Furthermore, the application also includes the step of shielding the side of the perovskite scintillator material facing the radiation source, thereby preventing large reflected light from affecting the use during the application process.
[0031] Furthermore, the shielding includes but is not limited to one or more of black tape shielding and aluminum plate shielding.
[0032] In yet another aspect, the present invention provides use of the perovskite scintillator material as described above in the fields of LED, anti-counterfeiting or laser.
[0033] The beneficial effects of the present invention are as follows:
[0034] In the perovskite scintillator material provided by the present invention, the organic cation RC 18 H 15 P + Providing large steric hindrance is conducive to the formation of glassy transparent perovskite, with a transmittance of up to 85% in the luminescent band, which can effectively reduce light scattering and improve spatial resolution. 3+As a luminescent center, it avoids self-absorption and improves optical properties. The material has high transparency, low light scattering and good spatial resolution under radiation, and can achieve clear radiographic imaging. In addition, the size of the material is controllable and can reach the centimeter level (for example, a circle with a diameter of 6 cm or more). In addition, the material does not need to be blended with an adhesive and is a self-supporting transparent scintillator with controllable shape. In the preparation method of the perovskite scintillator material of the present invention, a self-supporting transparent perovskite scintillator with controllable shape is realized for the first time, which provides a design principle for the next generation of transparent scintillators and promotes the development of non-destructive testing with low light scattering and high spatial resolution. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.
[0036] Figure 1 In Example 1, (C 22 H 24 P)SEM image and element mapping of 2SbCl5.
[0037] Figure 2 In Example 1, (C 22 H 24 P) Actual photos of transparent glass of different shapes of 2SbCl5.
[0038] Figure 3 Actual photographs of transparent glasses of different sizes in Example 1 are shown.
[0039] Figure 4 In Example 1, (C 22 H 24 X-ray absorption coefficients of P)2SbCl5 and some commercial inorganic scintillators.
[0040] Figure 5 In Example 1, (C 22 H 24 P)2SbCl5 at 2.3mGy air s -1 Radioluminescence spectrum after 30 s exposure to X-rays.
[0041] Figure 6 In Example 2, (C 19 H 18 P) Photo of 2SbCl5 transparent glass under X-ray.
[0042] Figure 7 In Example 3, (C 19 H 17 Photo of PCl)2SbCl5 transparent glass under X-ray.
[0043] Figure 8 In Example 6, (C 22 H 24 P)2Sb 0.5 Bi 0.5 Cross-sectional scanning electron microscope image of Cl5 transparent glass. DETAILED DESCRIPTION
[0044] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0045] Example 1
[0046] Based on the large steric hindrance (C 22 H 24 P)2SbCl5 transparent zero-dimensional perovskite scintillator material is prepared by the following method:
[0047] (C 22 H 24 P) Synthesis of 2SbCl5: First, weigh C and SbCl5 in a molar ratio of 2:1 on an analytical balance. 22 H 24 Solid raw materials of PCl709.07mg and SbCl3 228.12mg were ground into powder and mixed evenly and placed in a high temperature resistant glass dish. Then they were placed on a heating table and heated to 200℃ and then kept warm for 2h. It can be observed that all the solid powders have become molten. Then the molten melt was transferred to a graphite mold for cooling. After the melt was cooled for 15min, a transparent glass scintillator (C 22 H 24 P)2SbCl5. The thickness and shape of the final transparent scintillator can be controlled by controlling the volume of the melt poured into the mold and the shape of the mold. After demolding, a brightly luminous transparent glass scintillator can be obtained.
[0048] like Figure 1 As shown: the synthesized (C 22 H 24 The surface of P)2SbCl5 scintillator is smooth and even, and the elements such as C / Sb / Cl / P are evenly distributed; Figure 2 Shown are different shapes (C 22 H 24 P)2SbCl5 transparent glass. It can be seen that the glass surface is smooth and flat, and the transparency is very high. Figure 3 The large area (C) with a diameter of 6 cm and 3 cm prepared in this example is shown.22 H 24 P)2SbCl5 transparent glass physical picture (it should be noted that Figure 3 The Chinese and English words that appear in the text are used as background to reflect the transparency of glass and have no other meaning. ).
[0049] Performance test: at 2.3mGy air s -1 Under X-ray irradiation, exposure for 30s, 1.8mm (C 22 H 24 The resolution of P)2SbCl5 transparent glass can reach 25lp / mm, and its radioluminescence spectrum is shown in Figure 4.
[0050] The (C 22 H 24 The X-ray absorption coefficient of P2SbCl5 scintillator and commercial inorganic scintillators such as BGO, YAG:CE, Si, etc. Figure 5 As shown. Figure 5 It can be seen that (C 22 H 24 P)2SbCl5 transparent glass at 2.3mGy air s -1 The radioluminescence spectrum with a peak value of 635 nm was obtained by exposing to X-ray for 30 s, indicating that (C 22 H 24 P)2SbCl5 transparent glass has scintillating properties.
[0051] Example 2
[0052] The preparation process is the same as that of Example 1, except that:
[0053] In Example 2 (C 19 H 18 In the preparation of P2SbCl5, 709.07 mg of C 22 H 24 PCl was changed to 625.54 mg C 19 H 18 PCl, and then heated to 190℃ and kept warm for 2.5h, and then poured into the graphite mold. After demoulding, a 2.0mm thick (C 19 H 18 P)2SbCl5 self-supporting glass product.
[0054] Performance test: at 10.2mGy air s -1 Under X-ray irradiation, exposure for 60s, Figure 6It can be seen that the glass product has bright luminescence under X-rays, and the resolution can reach 20lp / mm.
[0055] Example 3
[0056] The preparation process is the same as that of Example 1, except that:
[0057] In Example 3 (C 19 H 17 In the preparation of PCl)2SbCl5, 709.07 mg of C 22 H 24 PCl was changed to 694.44 mg C 19 H 17 PCl2, then heated to 180℃ and kept warm for 2.0h, and then poured into the graphite mold. After demoulding, a 2.2mm thick (C 19 H 17 PCl)2SbCl5 self-supporting glass product.
[0058] Performance test: at 2.3mGy air s -1 Under X-ray irradiation, exposure for 60s, Figure 7 It can be seen that the glass product has bright luminescence under X-rays, and the resolution can reach 20lp / mm.
[0059] Example 4
[0060] The preparation process is the same as that of Example 1, except that:
[0061] In Example 4 (C 20 H 20 In the preparation of OP2SbCl5, 709.07 mg of C 22 H 24 PCl was changed to 685.60 mg C 20 H 20 OPCl2, then heated to 210℃ and kept warm for 1.0h, and then poured into a graphite mold. After demoulding, a 1.9mm thick (C 20 H 20 OP)2SbCl5 self-supporting glass product.
[0062] Performance test: at 2.3mGy air s -1 Under X-ray irradiation and exposure for 60 seconds, the glass product has bright luminescence under X-rays, and the resolution can reach 20lp / mm.
[0063] Example 5
[0064] The preparation process is the same as that of Example 1, except that:
[0065] In Example 5 (C 26 H 24 In the preparation of P2SbCl5, 709.07 mg of C 22 H 24 PCl was changed to 805.80 mg C 26 H 24 PCl, and then the heating temperature was changed to 190℃ and kept at this temperature for 3.0h. After demoulding, a 2.5mm thick (C 26 H 24 P)2SbCl5 self-supporting glass product.
[0066] Performance test: at 2.3mGy air s -1 Under X-ray irradiation, the glass product has bright luminescence under X-ray exposure for 60s, and the resolution can reach 20lp / mm. Under neutron irradiation, bright luminescence can be obtained.
[0067] Example 6
[0068] Based on the large steric hindrance (C 22 H 24 P)2Sb 0.5 Bi 0.5 The Cl5 transparent perovskite scintillator material is prepared by the following method:
[0069] (C 22 H 24 P)2Sb 0.5 Bi 0.5 Synthesis of Cl5 transparent perovskite scintillator: First, weigh C and C in a molar ratio of 2:0.5:0.5 on an analytical balance. 22 H 24 Solid raw materials of PCl 709.07 mg, SbCl3 114.06 mg and BiCl3 157.67 mg were ground into powder and mixed evenly and placed in a high temperature resistant glass dish. Then they were placed on a heating table and heated to 200 ° C. Then they were kept warm for 3.5 hours. It can be observed that all the solid powders have become molten. Then the molten melt was transferred to a graphite mold for cooling. After the melt was cooled for 30 minutes, a transparent glass scintillator (C 22 H 24 P)2Sb 0.5 Bi 0.5Cl5. The thickness and shape of the final transparent scintillator can be controlled by controlling the volume of the melt poured into the mold and the shape of the mold. After demolding, a transparent glassy scintillator with a thickness of 2.1 mm and bright light can be obtained.
[0070] like Figure 8 As shown: the synthesized (C 22 H 24 P)2Sb 0.5 Bi 0.5 The cross section of the Cl5 scintillator is smooth and flat, with no obvious impurities.
[0071] Performance test: at 2.3mGy air s -1 Under X-ray irradiation, exposure for 60s, glassy state (C 22 H 24 P)2Sb 0.5 Bi 0.5 Cl5 emits brightly under X-rays, with a resolution of up to 20lp / mm.
[0072] Example 7
[0073] The preparation process is the same as that of Example 6, except that:
[0074] In Example 8 (C 26 H 24 P)2Sb 0.5 In 0.5 In the preparation of Cl5, 709.07 mg of C 22 H 24 PCl was changed to 805.80 mg C 26 H 24 PCl, BiCl3 157.67mg was replaced by InCl3 110.59mg, and then the heating temperature was changed to 190℃ and kept warm for 3.0h. After demolding, a 2.2mm thick (C 26 H 24 P)2SbCl5 self-supporting glass product.
[0075] Performance test: at 2.3mGy air s -1 Under X-ray irradiation, the exposure time is 60s, and the X-ray has bright luminescence, and the resolution can reach 20lp / mm.
[0076] Example 8
[0077] The preparation process is the same as that of Example 6, except that:
[0078] In Example 8 (C 21 H 20O2P)2Sb 0.8 Bi 0.2 In the preparation of Cl5, 709.07 mg of C 22 H 24 PCl was changed to 741.62 mg C 21 H 20 O2PCl, 114.06mg of SbCl3 was changed to 182.50mg, 157.67mg of BiCl3 was changed to 63.07mg, and then the heating temperature was changed to 180℃, and kept warm for 1.5h, and then poured into a graphite mold. After demolding, a 2.2mm thick (C 21 H 20 O2P)2Sb 0.8 Bi 0.2 Cl5 self-supporting glass product.
[0079] Performance test: at 2.3mGy air s -1 Under X-ray irradiation and exposure for 60 seconds, the glass product has bright luminescence under X-rays, and the resolution can reach 20lp / mm.
[0080] Comparative Example 1
[0081] The preparation process is the same as that of Example 1, except that:
[0082] In Comparative Example 1 (C 16 H 36 In the preparation of N)2SbCl5, 709.07 mg of C 22 H 24 PCl was changed to 555.84 mg C 21 H 20 O2PCl, the heating temperature was changed to 180℃, and the temperature was kept for 1.5h, and then poured into the graphite mold. After demoulding, a 1.6mm thick and smooth surface (C 16 H 36 N)2SbCl5 self-supporting white opaque product.
[0083] Performance test: at 2.3mGy air s -1 Under X-ray irradiation, the white opaque product was exposed for 60 seconds and basically did not emit light under X-ray, and the resolution could reach 2.5lp / mm. Compared with Example 1, it shows that the RC 18 H 15 PX replaced by C 16 H 36 When NCl is used, it is impossible to synthesize the large-area transparent glass scintillator of the present invention, and the resolution is reduced by nearly ten times compared with other embodiments.
[0084] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A large-area transparent Sb-based and doped perovskite scintillator material, characterized in that: The general formula of the perovskite scintillator can be: (RC 18 H 15 P)2Sb y M 1-y X5; Wherein, R is selected from one or more of -CH3, -CH2Cl, -CH2CH3, -CH2OCH3, -(CH2)3CH3, -CH2C6H4CH3 and -C6H5; The M is a metal ion selected from the B-site doping ions; The X is selected from Cl - Br - and I - One or more of the following; The y is selected from 0-1, and is not 0.
2. The perovskite scintillator material according to claim 1, characterized in that: The M is selected from Bi 3+ 、In 3+ and Eu 3+ One or more of the .
3. The method for preparing the perovskite scintillator material according to any one of claims 1 to 2, characterized in that: The perovskite scintillator material is prepared by a melting method.
4. The preparation method according to claim 3, characterized in that: The preparation method comprises the following steps: The RC with a molar ratio of 2:y:1-y 18 H 15 Solid raw materials of PX, SbX3 and MX3 are ground into powder and mixed to obtain a mixture; The mixture is heated until all the solid powder is converted into a molten mixture; Cooling the molten mixture in a mold to obtain the scintillator material; Wherein, the definitions of y, R, X, and M are as described in claim 1.
5. The preparation method according to claim 4, characterized in that: The heating temperature ranges from 100 to 350°C.
6. The preparation method according to claim 4, characterized in that: The cooling method is natural cooling, air cooling or liquid cooling, and the cooling time is 5-15 minutes.
7. Application of the perovskite scintillator material according to any one of claims 1 to 2 in the field of radiation detection imaging.
8. The use according to claim 7, characterized in that: The rays are selected from one or more of soft X-rays, hard X-rays and neutrons.
9. The use according to claim 7, characterized in that: The application also includes the step of shielding the side of the perovskite scintillator material facing the radiation source.
10. Use of the perovskite scintillator material according to any one of claims 1 to 2 in the fields of LED, anti-counterfeiting or laser.
Citation Information
Patent Citations
Perovskite composite scintillator and preparation method and application thereof
CN112852414A
Hydrogen-rich two-dimensional perovskite fast neutron scintillator material and preparation method and application thereof
CN115074116A
Application of antimony halide based on organic-inorganic hybridization in X-ray detection and imaging
CN115873035A
Perovskite scintillator and application thereof in X-ray imaging scintillation screen
CN116478686A
Antimony doping-based chiral double-ligand indium-based hybrid halide perovskite material as well as preparation method and application thereof
CN116715638A